Rubella Vaccine Persistence Within Cutaneous Granulomas in Common Variable Immunodeficiency Disorder. (June 2020) - Bender, Nicole R.; Cardwell, Leah A.; Siegel, Dawn; Sokumbi, Olayemi
Abstract : Abstract: Common variable immunodeficiency disorder is a primary immunodeficiency disorder characterized by reduced levels of serum immunoglobulins and impaired antibody response. This condition may be associated with development of noninfectious granulomatous dermatitis of the skin which may be disfiguring and destructive. There are no published guidelines for the treatment of cutaneous granulomas in this patient population. In recent studies, rubella virus–positive cells in granulomas were localized to M2 macrophages which have an important role in wound healing and the secretion of immunoregulatory cytokines. We present a case of treatment-refractory, disfiguring common variable immunodeficiency disorder–associated granulomatous dermatitis. Immunofluorescence microscopy of the biopsy specimen confirmed the presence of rubella vaccine capsid proteins in M2 macrophages within the granuloma, a newly recognized phenomenon in this patient population. This knowledge may serve to identify future therapeutic targets or preventative strategies for granulomatous dermatitis in patients with primary immunodeficiency disorder.